AROME–NWC: a new nowcasting tool based on an operational mesoscale forecasting system. (3rd December 2014) - Auger, Ludovic; Dupont, Olivier; Hagelin, Susanna; Brousseau, Pierre; Brovelli, Pascal
<x xml:space="preserve">Abstract</x> The AROME–NWC nowcasting system has been developed in order to cover the nowcasting 0–6 h range. It is based on the existing AROME mesoscale model, from which the lateral boundary conditions and the first‐guess file are taken. The difference between those two systems is basically the observation window length and a very short cut‐off time. Studies have been carried out to show that in practice it is not necessary to compute a set of background‐error statistics matrices as a function of the forecast lead time of the first‐guess file. The spin‐up of the system has been proven to be small and the 15 min cut‐off to be long enough to keep a good forecast quality. This nowcasting system has been validated against the operational mesoscale model AROME: it has been shown that it performs better for nowcasting ranges as regards temperature, humidity and wind, due to its use of more recent observations. The precipitation forecasts are less satisfactory, with some improvement during the day and some degradation at night.